Chinese Language and Identity in the Dragon Boat Festival within the Context of Cultural Tourism in Than Nam Thip Subdistrict, Betong District, Yala Province - แซ่ชั้น วันวิวาห์; บุญแล วิจิตรา; บรรพโต ไพลิน; พัฒน์แก้ว รัตตา; เหิกขุนทด ประภาศรี (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to: 1) examine the linguistic meanings embedded in the cuisine of the Dragon Boat Festival within the Thai-Chinese community in Than Nam Thip Subdistrict, Betong District, Yala Province; and 2) analyze Chinese cultural identity and its connection to cultural tourism. This study employed a qualitative research approach, utilizing in-depth interviews and document analysis. Data were collected from 10 key informants, including community leaders, Thai-Chinese elders, Bac-chang (zongzi) entrepreneurs, and tourism officials. The data were analyzed using content analysis and interpretive approaches based on the language and cultural framework. The findings for the first objective revealed that language within the context of the Dragon Boat Festival functions not merely as a communication tool, but as a semiotic system reflecting the community’s cultural meanings. The term “Bac-chang,” a loanword from the Hokkien Chinese dialect, serves as a linguistic symbol that preserves ethnic traces and the collective memory of the Thai-Chinese community in Betong. Regarding the second objective, the results indicated that the Dragon Boat Festival serves as a social space reflecting the construction and negotiation of Chinese identity within the multicultural context of the southern border. The community maintains its Chinese roots through rituals, language, and culinary processes while simultaneously adapting to the contemporary Thai social context. The identity manifested through the festival’s language and cuisine can be further developed into cultural capital, with the potential to promote cultural tourism in the area. In conclusion, language, identity, and cultural tourism are interrelated through a dynamic process: language serves as the foundation for meaning-making, these meanings shape identity, and a robust identity can be transformed into cultural capital that significantly enhances the value and potential of cultural tourism in a multicultural borderland.